Vocabulary Skills of Grade 8 Students as Basis for the Development of Booklet for Filipino Vocabulary Learning - HERMONIO, MAY RALYN (International Journal of Arts, Sciences and Education, 2025)
Enhancing students’ vocabulary helps in developing clear and right connection of ideas in communication. This study aimed to determine the level of proficiency in Filipino vocabulary of Grade 8 students at Koronadal National Comprehensive High School for the academic year 2024-2025, basis for developing a booklet that will contain vocabulary enhancement methods such as Anagram, Code Breaker, Context Clues, Hyponym, and Lexical Analysis to improve vocabulary learning. The research problem focuses on the lack and weakness of students in defining or interpreting words and statements in Filipino with proper understanding. Using Descriptive-Developmental design, the study employed descriptive statistics, t-test, and a five-point rating scale to analyze the data. The respondents were chosen using Total Enumeration and was assessed using test that contains denotation and connotation questions. Based on the result, a booklet was developed and assessed by the expert teachers using evaluation tool to determine the validity and acceptability. Results displayed that the level of proficiency among students in Filipino vocabulary is very low while the validity and acceptability of booklet is very high. Overall, the study concludes that the booklet (TalasaPamamaraan) is a valid and acceptable tool for teaching and learning process. The output of the study may serve as instructional material for developing teaching and learning strategies in vocabulary enrichment.